Adsorption of Cu (II) and Cd (II) from Wastewater by Sodium Alginate Modified Materials - Yingying Zhao; Linchuan Zhan; Zhongjun Xue; Kianpoor Kalkhajeh Yusef; Hongxiang Hu; Mengjun Wu (Journal of Chemistry)
Natural macromolecule adsorbing materials are alternatives for remediation of heavy metals’ polluted waters. In this study, sodium alginate composite gel (SACL) was synthesized from sodium alginate (SA), polyethylene glycol oxide (PEO), and nanomaterials to remove wastewater Cu (II) and Cd (II). The adsorption efficiency of SACL was analysed in relation to the contact time, initial concentrations of metal ions, temperature, adsorbent dosage, and solution pH. Three models, i.e., kinetic model, isothermal adsorption model, and thermodynamic model, were used to fit the experimental data. Our results showed that the highest removal rates of Cu (II) and Cd (II) from wastewater were 96.8% and 78%, respectively, under the condition of the best liquid-solid ratio of 12.5 ml·g−1, and the contact time of 180 min (25°C). Overall, the SACL adsorption of Cu (II) and Cd (II) was spontaneous. The adsorption kinetics and the isothermal adsorption were fitted well with the pseudo-second-order kinetic equation and Langmuir equation, respectively. Combined with SEM-EDS and FTIR analysis, results suggested that SACL adsorbs wastewater Cu (II) and Cd (II) mainly through chemical reaction on its surface area. Altogether, this work concludes on SACL as an efficient and ecofriendly adsorbent for wastewater Cu (II) and Cd (II).